Developing and Pilot Testing of a Mini Massive Open Online Course (MOOC) on Occupational Epidemiology. Issue 5 (15th May 2022) - Braeckman, Lutgart; Hermans, Linda; D'Hulster, Leon; Van de Cauter, Joy; Verbrugghe, Mathieu
Abstract : Creating a Massive Open Online Course (MOOC) was a very satisfying experience and helped us renew our view on medical education. Given the costs in terms of time and money to develop one, we believe that interdisciplinary and international collaboration would improve the number and quality of future MOOCs especially in the field of occupational health and epidemiology. Abstract : Objective: Massive Open Online Courses (MOOCs) offer a flexible method of providing education to large numbers of people around the world. This study aimed to develop and pilot test a mini MOOC in order to teach knowledge and skills in occupational epidemiology. Methods: Using instructional design principles, an open online course was developed. Results: Four modules have been designed and delivered in a pilot version requiring an 8-hour time commitment. Thirty postgraduate students evaluated different aspects of the MOOC. They appreciated the active learning approach, gave high rates of approval for learning effects and structure but would welcome more feedback and interaction. Conclusions: Although students were satisfied, developing the MOOC entailed a considerable amount of time. A multi-institutional approach and international collaboration would be beneficial to improve the present MOOC and develop new ones.